A qualitative study on overdose response in the era of COVID-19 and beyond: how to spot someone so they never have to use alone - Melissa Perri; Natalie Kaminski; Matthew Bonn; Gillian Kolla; Adrian Guta; Ahmed M. Bayoumi; Laurel Challacombe; Marilou Gagnon; Natasha Touesnard; Patrick McDougall; Carol Strike (BMC, 2021)
Abstract Background Spotting is an informal practice among people who use drugs (PWUD) where they witness other people using drugs and respond if an overdose occurs. During COVID-19 restrictions, remote spotting (e.g., using a telephone, video call, and/or a social media app) emerged to address physical distancing requirements and reduced access to harm reduction and/or sexually transmitted blood borne infection (STBBI's) prevention services. We explored spotting implementation issues from the perspectives of spotters and spottees. Methods Research assistants with lived/living expertise of drug use used personal networks and word of mouth to recruit PWUD from Ontario and Nova Scotia who provided or used informal spotting. All participants completed a semi-structured, audio-recorded telephone interview about spotting service design, benefits, challenges, and recommendations. Recordings were transcribed and thematic analysis was used. Results We interviewed 20 individuals between 08/2020-11/2020 who were involved in informal spotting. Spotting was provided on various platforms (e.g., telephone, video calls, and through texts) and locations (e.g. home, car), offered connection and community support, and addressed barriers to the use of supervised consumption sites (e.g., location, stigma, confidentiality, safety, availability, COVID-19 related closures). Spotting calls often began with setting an overdose response plan (i.e., when and who to call). Many participants noted that, due to the criminalization of drug use and fear of arrest, they preferred that roommates/friends/family members be called instead of emergency services in case of an overdose. Both spotters and spottees raised concerns about the timeliness of overdose response, particularly in remote and rural settings. Conclusion Spotting is a novel addition to, but not replacement for, existing harm reduction services. To optimize overdose/COVID-19/STBBI's prevention services, additional supports (e.g., changes to Good Samaritan Laws) are needed. The criminalization of drug use may limit uptake of formal spotting services.